RESPON MASYARAKAT TERHADAP PELAYANAN TRANSMETRO PEKANBARU - Dessi Permata Sari; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Transmetro is public bulk transportation. According to Pekanbaru Statistics Agency, in 2016, Residents of Pekanbaru city currently numbered as 1,064,566 and will increase every year in the future . Currently the number of private vehicles is not proportional to the number of roads, and it will impact to traffic jam, fuel wastage, noise, and high levels of pollution. To solve this problem, the government of Pekanbaru triggered a policy of urban transportation service named Transmetro Pekanbaru. The theory used in this research is response theory. according to Soemanto The data analyst is done by descriptive with quantitative approach, the data retrieval technique in this research is the accidental sampling, that the every resident who by chance met the researcher can be used as sample. and it must suitable to source of data, Where respondents amounted to 80 people consisting of 10 people per route, which Transmetro has 8 routes, this research is done at the bus stop and inside of Transmetro bus Pekanbaru because by doing research at Transmetro bus stops and buses are expected to get the data needed by researchers . From the results of research in the field in the know that the public response to the service of bus stop facilities is not good, the response to the bus facility service is good and the response to the employee service is good. Dissatisfactory factors or transmetro weaknesses are: the employee is not friendly, driver reckless , the waiting period of busses is too long, priority seats are less in with actual and uneven pathways that pass by Transmetro. However, there are some things that become excess or the factor of satisfaction to transmetro, those are: good employee service, affordable price with wide reach, clean bus and equipped with AC facility and cctv camera, and only transmetro which has wide reach point. But public still have lack awareness of transmetro advantages and facilities.Keywords: Response, Service, Transmetro Pekanbaru